Thermal behavior of siliceous and ferro-siliceous sacrificial concrete subjected to elevated temperatures. (5th April 2016) - Chu, Hong-yan; Jiang, Jin-yang; Sun, Wei; Zhang, Mingzhong
Abstract: Siliceous and ferro-siliceous sacrificial concrete (SC) are designed to reduce the leakage potential of radioactive materials in case of severe nuclear accidents. This paper presents an investigation on thermal behavior and damage evolution of SCs subjected to high temperatures. In this study, the microstructure, porosity, high-temperature integrity, mass loss, compressive strength, splitting tensile strength, and thermal diffusivity of SCs were investigated at different elevated temperatures up to 1000 °C. Using ultrasonic testing technique, variations of ultrasonic pulse velocity (UPV) propagation in SCs exposed to different high temperatures were obtained. According to definition of damage, a relationship between damage of SC and UPV was derived, eventually concluding a correlation between the damage of SC and high temperatures that SC subjected to. It was found that, (1) the SCs designed have very good performances, and are suitable for use in practice; (2) with temperature increasing, the thermal diffusivity of SCs decreases continually, and the damage evolution of SCs can be described by a Weibull distribution model. Graphical abstract: Highlights: The SCs designed have very good performance, and are suitable for use in practice. The porosity of SCs increases continually with the increase of temperature. The mechanical properties of SCs are highly deteriorated due to high temperature. The thermal diffusivity of SCs displays a rapidly decreasing process in 200–500 °C. The damage evolution of SCs can be described by a Weibull distribution model.